Chinese and South Korean Children’s Moral Reasoning Regarding the Fairness of a Gendered Household Labor Distribution - Midgette, Allegra J. (Dev Psychol, 2019)
This study explored age-related changes in Chinese and Korean children’s fairness judgments and reasoning regarding the gendered division of household labor. The majority of previous research on this issue has focused on adults’ experiences and been conducted in Western countries. Interviews were conducted with 133 children, 65 Chinese and 68 South Korean, ages of 9–11 (N=48), 12–14 (N=43), and 16–18 (N=42). Despite country differences in women’s involvement in the workforce in both countries women do most of the housework. The majority of participants across ages evaluated a hypothetical scenario in which the mother did most of the work as unfair, and endorsed as fair a hypothetical scenario in which housework was divided evenly. Developmental effects were found with younger children in both countries employing more equality justifications and adolescents providing more social convention justifications. In both countries children described their mother as doing the majority of the housework, and in contrast with their judgments about hypothetical situations, were evenly divided overall in their evaluations of whether this unequal distribution in their actual families was fair. Korean children were more likely to view their family’s division unfair than Chinese children, and were more likely to employ equality justifications in support of those judgments. Unexpectedly, across countries moral reasoning in the form of expectations of equity rather than gender stereotyping was employed to justify an unequal division of labor. This study’s findings suggest the value of investigating children’s fairness judgments and moral reasoning regarding both hypothetical and actual situations.